Logic based reactive system (LBR) - a new software design approach for automation and equipment controls - Goh, Lay Siong. (2008)
The objective of this dissertation is to discuss and evaluate the possibility of implementing Logic Based Reactive System (LBR) on PC based embedded system using conventional software languages such as C, Visual Basic, for machines and equipment installed at the manufacturing industries.